Magnetic resonance imaging at one year for detection of postoperative residual cholesteatoma in children: Is it too early?. Issue 8 (August 2015) - Lecler, A.; Lenoir, M.; Peron, J.; Denoyelle, F.; Garabedian, E.N.; Pointe, H. Ducou le; Nevoux, J.
Abstract Objective To compare the residual cholesteatoma detection accuracy of diffusion-weighted (DW) and T1 delayed sequences for magnetic resonance at one year postoperative with second-look surgery in pediatric patients who have undergone primary middle ear surgery for cholesteatoma. Methods This was a prospective monocentric consecutive study conducted in a tertiary academic referral center. Children were referred for MR imaging (MRI) one year after surgery. A 1.5 T MRI was utilized, using nonecho-planar DW images and delayed gadolinium-enhanced T1-weighted images. Accuracy of magnetic resonance imaging was assessed by two radiologists before surgery. Interobserver and intraobserver agreements were assessed using the κ test. Magnetic resonance imaging data were compared with surgery, which was considered as the gold standard. Results Twenty-four consecutive unselected pediatric patients were included. Sensitivity, specificity, positive predictive value, and negative predictive value for the first observer were of 40%, 86%, 67%, and 67%, respectively, and those for the second observer were 30%, 86%, 60%, and 63%, respectively. The only two cholesteatoma with a size superior to 3 mm were diagnosed before surgery, but the majority of small cholesteatoma were not detected. Conclusions MRI is a key examen to diagnosed the residual cholesteatoma but is limited by the size of the lesion under 3 mm. Delaying the realization of MRI during follow-up could increase sensitivity, thus avoiding misdiagnosis as well as unnecessary second look surgery.